A158 LACK OF DIFFERENCE OF COLONIC CURVATURE IN SUPINE VERSUS PRONE PATIENT POSITIONS, IN NORMAL AND HIGH BMI INDIVIDUALS, AS ASSESSED BY QUANTITATIVE ASSESSMENT OF COMPUTED TOMOGRAPHY COLONOGRAPHY. (26th February 2020) - Tan, P; Laframboise, J; Barr, K; Anvari, H; Ungi, T; Fichtinger, G; Scott, C; Bechara, R; Hookey, L
Abstract: Background: Dynamic positional changes during colonoscopy are commonly used in clinical practice, in particular moving from side to side. It has been shown to improve both adenoma detection rates as well as cecal intubation times. However, perhaps due to an additional level of inconvenience, there have been few studies comparing the anatomy and changes in colonic curvature when patients are in the prone position, which may help to prevent anterior bowing of the scope, particularly in patients with high body mass index (BMI). Aims: To compare both the number of colonic curves and degree of change in curves with patients in supine versus prone positioning during computed tomography colonography (CTC). Methods: 75 CTC studies, obtained between January and April 2017 at Hotel Dieu Hospital in Kingston, Ontario, were screened and included based on image quality and adequacy of distention. Per standardized protocol, all patients undergoing CTC are imaged both in supine and prone positioning. Using an automated computer algorithm process developed for this study, curves were identified and measured via centerline points placed digitally through the colonic lumen, and compared between supine and prone patient positioning. Results: 75 colonographies were examined. The mean age was 68 years and 37/75 were male. BMI data was available for 56 patients, with mean BMI 29.4 (SD 5.7). There were no significant differences in total mean degrees of curvature between supine and prone positions [75.3 (SD 13.5) vs. 77.3 (SD 15.3), p=0.07], nor a significantly higher total number of curves >100 degrees [4.0 (SD 2.0) vs. 4.5 (SD 2.3), p=0.14]. No significant correlation was seen between BMI and change in position (correlation factor 0.2, p=0.13). Conclusions: No significant differences were found between the two positions during CT colonography. This certainly calls into question the strategy of starting in prone position, even in higher BMI patients. However, CT colonography doesn't account for changes that can occur during colonoscopy, as the scope itself can dynamically affect angulations within the colon. Funding Agencies: None